Physical Education Teacher Attitudes toward the Stimulation of Student Higher-Order Thinking Skills (Universitas Pendidikan Indonesia, 2025)
Higher order thinking skills (HOTS) are essential to prepare students to face challenges and make literacy activities more meaningful. However, several studies reported that Indonesian student HOTS are still low. HOTS need stimulus to develop optimally, especially for school age students (10-18 years) because, at that age, children are not yet able to think at a high level by themselves and the activity for stimulating HOTS in students is greatly affected by the teacher attitude to the value of stimulating HOTS itself. This study aimed to compare the attitude of Physical Education (PE) teachers in stimulating HOTS of students. The design of research used in this study was comparative design. The sample involved PE teachers teaching in West Sumatra province, totaling 129 people. The samples were drawn using self-selection sampling. The instrument used to measure teacher attitudes was the SHOT questionnaire. Data analysis was conducted with Mann-Whitney U test and Kruskal-Wallis test. The results showed that the teacher attitudes based on school level and teaching experience obtained Sig 0.05, while the teacher attitudes according to certification status obtained Sig 0.05. It concludes that the attitude of teachers based on school level and teaching experience was not significantly different, while the teacher attitudes according to certification status was significantly different.